MODIFIKASI NASTAR “BIONSTAR” BERBASIS TEPUNG UBI UNGU DAN TEPUNG ALMOND UNTUK PENDERITA DIABETES MELITUS TIPE 2 - Hernawati, Hernawati; Suprihartono, Fred Agung; Gumilar, Mulus; Fitria, Mona (Poltekkes Kemenkes Bandung, 2025)
In 2021, the International Diabetes Federation (IDF) reported that 537 million adults worldwide were living with diabetes mellitus, with a projected increase of 45% to 783 million by 2045. Indonesia ranks fifth among the ten countries with the highest number of cases. Low-glycemic index snacks can help slow the rise in blood glucose levels in diabetic patients. Modifying nastar using purple sweet potato flour and almond flour is expected to produce a high-fiber, low-glycemic snack suitable for individuals with type 2 diabetes. Purple sweet potato is rich in fiber and anthocyanins, while almond flour has a low glycemic index and contains polyunsaturated fatty acids (PUFA). This study aimed to determine the effect of purple sweet potato flour and almond flour formulation on the quality of nastar, including organoleptic properties, nutritional value, fiber content, and cost. The study used an experimental design with three formulations: F1 (80%:20%), F2 (70%:30%), and F3 (60%:40%). Organoleptic tests assessed color, aroma, taste, texture, and overall preference using 30 semi-trained panelists. Proximate tests were conducted to measure energy, protein, fat, carbohydrate, and fiber contents. Data were analyzed using the Kruskal-Wallis test.The results showed no significant differences (p > 0.05) in organoleptic attributes among the formulations. Formula F1 was the most preferred. Each 54 g serving of Bionstar contained 213 kcal energy, 3.54 g protein, 13.09 g fat, 20.39 g carbohydrates, and 1.32 g fiber, with a cost of IDR 6,883.4. It is recommended to add high-fiber ingredients such as legumes to improve fiber content.